Counseling Practices by Parents for Children Among Fishermen’s Families in Tanjung Tiram District, Batubara Regency, North Sumatra Province - Malia, Eka; Ok, Azizah Hanum; Al Farabi, Mohammad (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
This article discusses the existence of counseling practices carried out by parents towards children in fishing families in Tanjung Tiram District, Batubara Regency. The aim is to describe how parents carry out counseling activities for their children, even though it is not formal. This type of descriptive research with a qualitative approach was chosen to describe this problem. Primary data was taken by observation, interview, and documentation methods, while secondary data was taken from a review of several kinds of literature. The results obtained are the implementation of counseling practices by parents of fishing families in the form of loving children, protecting the family with a sense of comfort, respecting the rights and obligations of children and parents, instilling trust, and gathering for family discussions. The steps taken are creating good family relationships, listening wholeheartedly, solving problems, feeling the child's condition, being a good listener, helping to find